Pesticide residues alter taxonomic and functional biodiversity in soils - J. Köninger; M. Labouyrie; C. Ballabio; O. Dulya; V. Mikryukov; F. Romero; A. Franco; M. Bahram; P. Panagos; A. Jones; L. Tedersoo; A. Orgiazzi; et al. (Nature, 2026)
Abstract Pesticides are widely distributed in soils 1–3 , yet their effects on soil biodiversity remain poorly understood 4–7 . Here we examined the effects of 63 pesticides on soil archaea, bacteria, fungi, protists, nematodes, arthropods and key functional gene groups across 373 sites spanning woodlands, grasslands and croplands in 26 European countries. Pesticide residues were detected in 70% of sites and emerged as the second strongest driver of soil biodiversity patterns after soil properties. Our analysis further revealed organism- and function-specific patterns, emphasizing complex and widespread non-target effects on soil biodiversity. Pesticides altered microbial functions, including phosphorus and nitrogen cycling, and suppressed beneficial taxa, including arbuscular mycorrhizal fungi and bacterivore nematodes. Our findings highlight the need to integrate functional and taxonomic characteristics into future risk assessment methodology to safeguard soil biodiversity, a cornerstone of ecosystem functioning.